Pengaruh Pemberian Konsentrat yang Mengandung Rumput Laut Eucheuma cottonii Afkir Terfermentasi Terhadap Konsentrasi Amonia, pH dan VFA Rumen Sapi Bali Betina Muda yang diberi Pakan Dasar Silase Rumput Kume atau Fodder Jagung - Langsibo, Aprilia Marince; Jalaludin, Jalaludin; Nikolaus, Tara Tiba (Animal Agricultura, 2024)
This study was conducted to determine the effect of providing concentrate containing rejected fermented Eucheuma cottonii seaweed on ammonia (NH3), pH and VFA rumen of Bali heifer fed basal diet of Kume grass silage or corn fodder. This study used Latin Square Design (LSD) with 4 treatments and 4 periods as replications. The treatments used were: SKC0 = silage + concentrate containing unfermented seaweed Eucheuma cottonii, SKC0F = silage + concentrate containing fermented seaweed Eucheuma cottoni, FJK0= corn fodder + concentrate containing unfermented seaweed Eucheuma cottoni, FJK0F= corn fodder + concentrate containing fermented seaweed Eucheuma cottonii. The variables measured were ammonia (NH3) concentration, pH and VFA. The data obtained were analyzed using Analisys of Variance (ANOVA) and Duncan's multiple range test. The results showed that the treatments had no significant effect (P>0,05) on ammonia, pH and VFA concentration. It can be concluded that the providing of concentrates containing fermented seaweed Eucheuma cottonii does not affect on ammonia, pH ans VFA concentration of Bali heifer consuming basal diet of kume grass silage or corn fodder.